2011
DOI: 10.1245/s10434-011-2051-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving Symptoms and Quality of Life of Female Cancer Survivors: a Randomized Controlled Study

Abstract: The MBSR-based cancer recovery and wellness intervention improved the symptoms and quality of life of this largely breast cancer survivor population across a variety of cancer symptoms and quality-of-life measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 12 publications
1
91
0
8
Order By: Relevance
“…Components most commonly consisted are educational and psychological or psychosocial interventions (Pitceathly et al, 2009;Capozzo et al, 2010;Goerling et al, 2011;Lerman et al, 2011;Lurati et al, 2012). Due to complexity and individuality of psychological and physiological changes, researchers usually design their programs based on their own experiences and understandings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Components most commonly consisted are educational and psychological or psychosocial interventions (Pitceathly et al, 2009;Capozzo et al, 2010;Goerling et al, 2011;Lerman et al, 2011;Lurati et al, 2012). Due to complexity and individuality of psychological and physiological changes, researchers usually design their programs based on their own experiences and understandings.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese version of symptom checklist-90 (SCL-90) (Wang, 1984), a 90-item multidimensional self-report inventory aiming to evaluate a broad range of psychological problems and symptoms of psychopathology, was adopted as the major measurement for psychological status. The reliability, validity and utility of SCL-90 have been proved not only by psychiatric and psychological studies (Peveler et al, 1990;Schimitz et al, 1999;Prins et al, 2001), but also been demonstrated by studies in cancer patients (Derogatis et al, 1983;Tross et al, 1996;Lerman et al, 2011). The data from SCL-90 were calculated and compared with the normal range in Chinese reported by Jin et al (1986.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, survivorship has become a major focus of research aiming to minimize toxicity of treatments and decrease the incidence of iatrogenic complications (2). Secondary lymphedema is the most common longterm complication of surgery for solid tumors and occurs when lymphatic channels or lymph nodes are removed during cancer staging/treatment (3).…”
Section: Introductionmentioning
confidence: 99%
“…After examination of the titles and the abstracts, 138 studies met the inclusion criteria - 28 single armed trials [Table 1][32333435363738394041424344454647484950515253545556575859] and 110 randomized and nonrandomized controlled trials: 18 from 1996 to 2008 [Table 2],[606162636465666768697071727374757677] 34 from 2009 to 2012 [Table 3],[78798081828384858687888990919293949596979899100101102103104105106107108109110111] and 58 from 2013 to 2016 [Table 4]. [112113114115116117118119…”
Section: Resultsmentioning
confidence: 99%